2010
DOI: 10.2172/973409
|View full text |Cite
|
Sign up to set email alerts
|

EFRT M-12 Issue Resolution: Caustic-Leach Rate Constants from PEP and Laboratory-Scale Tests

Abstract: Revision Number Interim Change No. Effective Date Description of Change 0 0 8/14/09 Initial issue. Appendix C: Corrected a typographical error in Equation (C.1). As a response to a September 2009 CRESP review comment, revised the appendix to further explain the way in which the Monte Carlo method was applied and to reference information on the technical basis of the analytical uncertainties that were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…This R&T condition is discussed in Mahoney et al (2009) and Section 9 of this report for caustic leaching. It is discussed in Rapko et al (2009) and Section 11 in this report for oxidative leaching.…”
Section: Leaching Operationsmentioning
confidence: 96%
See 3 more Smart Citations
“…This R&T condition is discussed in Mahoney et al (2009) and Section 9 of this report for caustic leaching. It is discussed in Rapko et al (2009) and Section 11 in this report for oxidative leaching.…”
Section: Leaching Operationsmentioning
confidence: 96%
“…Pretreatment Engineering Platform operations were evaluated by Mahoney et al (2009) against these guidelines. It was concluded that, to the extent that the PEP design and operation allowed, caustic leaching for Integrated Test A was prototypic of the PTF.…”
Section: Caustic Leaching In Tank T01a/b (Functional Test and Integramentioning
confidence: 99%
See 2 more Smart Citations
“…There were two tests for PEP Test D with different amounts of permanganate added (Section 6.5). The analysis of test results presented in this section is reported in WTP-RPT-186 (Mahoney et al 2009) and WTP-RPT-188 (Rapko et al 2009). Integrated PEP Test C was deleted from the scope of the testing (ICN-TP-RPP-WTP-506_R0.2).…”
Section: Pep Parallel Leaching Testsmentioning
confidence: 99%